2015
DOI: 10.1007/s11249-015-0561-y
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Thermo-Desorption of Perfluoropolyether Lubricant from the Surface of a Heat-Assisted Magnetic Recording Disk: Lubricant Evaporation and Diffusion

Abstract: Heat-assisted magnetic recording (HAMR) storage technology will thermally stress the lubricant film typically applied to the storage disk surface. Different lubricant loss and morphology change mechanisms have been hypothesized to occur during information writing. A loss to of the lubricant film will dramatically affect its overall mechanical and chemical performance of the headdisk interface, decreasing its reliability and its durability. Thus an all optical pump-probe method was used to study the effect of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…From a slider-disk interface perspective, the thermal stress is expected to challenge the robustness of today's protective carbon and boundary lubricant films. Numerous studies have been spawned to answer the question of whether or not the current carbon and lubricant "tribological layers" can survive HAMR technology [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…From a slider-disk interface perspective, the thermal stress is expected to challenge the robustness of today's protective carbon and boundary lubricant films. Numerous studies have been spawned to answer the question of whether or not the current carbon and lubricant "tribological layers" can survive HAMR technology [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…From strictly a boundary lubricant perspective, experimental studies have shown that laser heating removes lubricant film from the disk surface [2,8,9]. Depending upon the read-write duty cycle, the mobility of the boundary lubricant film, and the local supply of the lubricant film, reflow from the surrounding area into the thickness-depleted area may, or may not, occur at a fast enough rate to maintain tribological robustness under HAMR conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most experimental laser irradiation studies on PFPEs have been conducted on much larger ~ 10 µm (10,000 nm) spot size so HAMR-realistic length scales have not yet been approached. Under these conditions, as much as several Å of lubricant film thickness could be removed depending upon laser power and exposure time [8][9][10][11]. Based upon these data, there is little doubt that HAMR disk lubricants with improved thermal stability will become an important lubricant design feature.…”
Section: Introductionmentioning
confidence: 99%